2001
DOI: 10.1080/02626660109492866
|View full text |Cite
|
Sign up to set email alerts
|

On the identification of ENSO-induced rainfall and runoff variability: a comparison of methods and indices

Abstract: It is known that the El Nino Southern Oscillation (ENSO) phenomenon induces marked climate variability across many parts of the world. However, in seeking useful relationships between ENSO and climate, several indices are available. In addition to the choice of index, previous studies assessing ENSO effects have employed a range of different methods to classify periods as El Nino, La Nina or Neutral. It is therefore clear that significant subjectivity exists in the adoption of ENSO classification schemes. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 12 publications
1
89
1
Order By: Relevance
“…The four dominant large-scale climate modes operating in the Southern Hemisphere are -ENSO (Chiew et al, 1998;Kiem and Franks, 2001;Verdon et al, 2004), which in this study is represented by the Oceanic Niño Index (ONI) from the United States National Oceanic and Atmospheric Administration (NOAA) Climate Prediction Centre (CPC) (www. cpc.ncep.noaa.gov).…”
Section: Indices Of Large-scale Climate Modesmentioning
confidence: 99%
“…The four dominant large-scale climate modes operating in the Southern Hemisphere are -ENSO (Chiew et al, 1998;Kiem and Franks, 2001;Verdon et al, 2004), which in this study is represented by the Oceanic Niño Index (ONI) from the United States National Oceanic and Atmospheric Administration (NOAA) Climate Prediction Centre (CPC) (www. cpc.ncep.noaa.gov).…”
Section: Indices Of Large-scale Climate Modesmentioning
confidence: 99%
“…Accordingly, the relationship identified between SEA hydroclimatology and the various large-scale climate drivers varies depending on the index and/or classification method chosen (Kiem and Franks, 2001). However, the conclusion that it is the interaction (s) between multiple large-scale climate phenomena that drives SEA climate is not sensitive to the choice of index or classification method.…”
Section: Large-scale Climate Modesmentioning
confidence: 99%
“…Kiem and Franks (2001) showed that the MEI outperformed the more traditional SOI and NINO3 indices in identifying ENSO-related changes in rainfall and runoff observations. The MEI can be used to classify ENSO events in various ways, including the approach of Chiew et al (1998), who used mean index values over twelve-month periods from April to March to define both El Niño and La Niña phases.…”
Section: Data and Working Assumptionsmentioning
confidence: 99%
“…The MEI can be used to classify ENSO events in various ways, including the approach of Chiew et al (1998), who used mean index values over twelve-month periods from April to March to define both El Niño and La Niña phases. The method used in this study follows one of the approaches of Kiem and Franks (2001); they used averages of monthly index values over six-month periods from October to March to distinguish annual ENSO phases and claim that this method is the most robust for identifying ENSO variability over the time period being investigated. In this manner, El Niño years are characterised as any year in which the six-month MEI average beginning in the previous October is above 0.5 and La Niña events as years in which this average is below 0.5.…”
Section: Data and Working Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation